Comparison of tenoscopic and ultrasonographic methods of examination of the digital flexor tendon sheath in horses - Edinger, J.; Möbius, G.; Ferguson, J. (Veterinary and Comparative Orthopaedics and Traumatology, 2005)
The purpose of this study was to compare sonographic and tenoscopic findings with the purpose of establishing the accuracy and limitations of ultrasonography as a non-invasive diagnostic modality in evaluating the DFTS and its enclosed tendons. The medical records from 22 horses which underwent tenoscopic desmotomy of the palmar/plantar annular ligament were evaluated in a retrospective study. The qualitative assessment of sonographic and tenoscopic findings were documented for the digital flexor tendon sheath (DFTS), the palmar/plantar annular ligament (PAL), the superficial digital flexor tendon (SDFT) and the deep digital flexor tendon (DDFT). The abnormalities diagnosed sonographically within the DFTS were verifiable tenoscopically with a sensitivity of 90.9% and a specificity of 53.8%. The positive predictive value of sonographic examination at the DFTS was 62.5%. The sensitivity of the sonographic examination at the PAL was 68.8%, the specificity was 50% and the positive predictive value 73.3%. Sonographic examination of the SDF tendons revealed abnormal findings in 12 tendons. The tenoscopic examination confirmed these findings on six tendons when they had a pronounced fibrillated or rough tendon surface or tear on the border. Six superficial flexor tendons and seven deep digital flexor tendons had abnormalities seen tenoscopically which were not visible on sonographic examination. Sonographic examination located lesions of the DDFT in four limbs. On tenoscopic examination the lesions could be detected in seven other DDF tendons, including signs of inflammation at the tendon surface that were not seen ultrasonographically (sensitivity 36.4%). Recognition of the limitations of sonographic results should be kept in mind so as not to misinterpret findings, especially if echogenic materials are observed.
Keywords: Horse; digital flexor tendon; digital flexor tendon sheath; annular ligament; tenoscopy; ultrasonography